Role of ozone nuleolysis in management of discogenic pain in lumbar and lumbosacral disc prolapse - Yadav, Kuldeep; Bhaskar, Priyesh; Jagetia, Anita; Kaif, Mohd. (International Surgery Journal, 2016)
Background: Discogenic low back pain is a common symptom. Over the years many percutaneous minimally invasive therapeutic modalities have evolved. Intradiscal oxygen-ozone therapy is one of them and has showed promising results. We undertook a prospective study to evaluate the therapeutic outcome of intradiscal oxygen-ozone therapy on patients with lumbar and lumbosacral disc prolapse in the Indian population. Methods: Fifty consecutive patients complying with selection criteria were included in this study with clinico-radiologic diagnosis of lumbar and/or lumbosacral disc prolapse. All patients received ozone-oxygen mixture in the disc, in neural foramen and root canal and in facet join region and para-vertebral muscles at concentration of 29-40 mcg/mL. Therapeutic outcome was assessed after four weeks, three months, and six months post-procedure, on visual analog scale (VAS), Oswestry low back pain disability questionnaire (ODI) and Modified MacNab methode. Results: Pain intensity was significantly reduced following treatment (from baseline mean VAS 8.46±0.67 to 3.8±1.29 at one month, at three months 3.1±0.7 and at six months follow up 3.78±1.13, p < 0.0001). Similarly the ODI and modified MacNab criteria showed a remarkable improvement in the functional status of the patients (p<0.05). No minor or major complications were observed in this case series. Conclusions: It can be concluded that oxygen-ozone treatment is highly effective in relieving low back pain due to lumbar and lumbosacral disc prolapse.